Pentafluorophenylammonium triflate: An effective and reusable organocatalyst for the one-pot preparation of 2,4-diaryl-5H-indeno[1,2-b]pyridin-5-one derivatives - A. Mohammed Hussain; S. Sheik Mansoor; K. Aswin; S.P.N. Sudhan (Journal of King Saud University: Science, 2014)
A new one-pot and efficient three-component condensation of 1,3-diphenyl-2-propen-1-ones (chalcones), 1,3-indandione, and ammonium acetate using pentafluorophenylammonium triflate (PFPAT) as catalyst for the synthesis of substituted 2,4-diaryl-5H-indeno[1,2-b]pyridin-5-one is described. The present methodology offers several advantages, such as good yields, atom economy, short reaction times and a recyclable catalyst with a very easy work up.